Exploring the Impact of Human Resource Management Practices on Employee's Retention: Evidence from the Food and Beverage Industry in the State of Qatar - Olawumi Dele Awolusi; Shirley Shamen Jayakody (Journal of Social and Development Sciences, 2022)
Employee turnover is stated as a huge issue concerning business organizations in Qatar. The organizations in the food and beverage industry of Qatar try to retain the employees by using suitable and appropriate human resource policies. Consequently, the paper analyzed the influence of human resources management practices on employee’s retention in the food and beverage industry of Qatar. In the present study, the researcher used a simple random sampling method to select the employees in the F&B industry in Qatar to minimize the chances of sampling error or fluctuations and biases in the data. According to the sample size calculation, 41 samples were used for data collection. But only 35 respondents were given responses to questionnaire filling. Therefore, 35 samples were only used in this study. Thus, a survey questionnaire was the research instrument. The questionnaire contained 14 close-ended questions, divided, into two sections, demographic and non-demographic. Considering the study objectives, the quantitative, data analysis method was applied in this study. The survey responses were converted into numeric values as those were collected through a replicable scale. Inferential, reliability, correlation and multiple regression analysis were applied to test the hypotheses. The study concluded that HR Recruitment policy, Training, and development program, Performance appraisal system; Reward system are important determinants of employee retention in the food and beverage industry of Qatar. Specifically, the reasons for increasing employee's turnover are lack of growth opportunities, poor communication, improper promotional activities, and misalignment of culture and value system, lack of decision-making ability, employee welfare, work-life imbalance and regular changes in job responsibilities. The study, therefore, recommended the following: greater employee’s involvement in the HRM policy formulation and implementation, improved employee’s compensation, social recognition, efficient top management support, as well as improved training and development in the food and beverage industry in Qatar.